2012
DOI: 10.1103/physrevd.85.054501
|View full text |Cite
|
Sign up to set email alerts
|

Confinement in G(2) gauge theories using the thick center vortex model and domain structures

Abstract: The thick center vortex model with the idea of using domain structures is used to calculate the potentials between two G(2) heavy sources in the fundamental, the adjoint and the 27 dimensional representations. The potentials are screened at large distances. This behavior is expected from the thick center vortex model since G(2) has only a trivial center element which makes no contribution to the average Wilson loop at the large distance regime. A linear potential is obtained at intermediate distances for all r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…However, the linear rise of the potentials for all representations at the intermediate distances was clearly observed in lattice gauge theory [18,26]. On the other hand, from the domain structure model, we have observed linear potentials between G(2) sources for different representations roughly proportional to the eigenvalue of the quadratic Casimir operator of the representation which is in agreement with the lattice results [27]. In our previous article [30], we have argued that the SU (2) and SU(3) subgroups of the G(2) gauge group may be responsible for the confinement potential of G (2).…”
Section: Jhep03(2015)016supporting
confidence: 88%
See 1 more Smart Citation
“…However, the linear rise of the potentials for all representations at the intermediate distances was clearly observed in lattice gauge theory [18,26]. On the other hand, from the domain structure model, we have observed linear potentials between G(2) sources for different representations roughly proportional to the eigenvalue of the quadratic Casimir operator of the representation which is in agreement with the lattice results [27]. In our previous article [30], we have argued that the SU (2) and SU(3) subgroups of the G(2) gauge group may be responsible for the confinement potential of G (2).…”
Section: Jhep03(2015)016supporting
confidence: 88%
“…The confinement regime has been increased [18] when the vacuum domains have been added to the model. In our previous papers [27,30], we have studied the role of the vacuum domain in G(2) gauge group which has one trivial center element, only. According to the center vortex theory, one does not expect confinement in a group without nontrivial center element.…”
Section: Static Potentials and Casimir Scalingmentioning
confidence: 99%
“…In fact, numerical simulations of this Yang-Mills theory have already been going on for some years [74][75][76][77][78][79][80][81][82][83][84][85]. Besides numerical studies, these peculiar features of G 2 Yang-Mills theory have also triggered analytical interest [86][87][88][89][90][91][92][93][94][95][96][97].…”
Section: Jhep03(2015)057mentioning
confidence: 99%
“…Using the thick center vortex model with the idea of vacuum domain structures, Deldar et al have found the potential between static color sources in the G 2 gauge group [5], [6], [7]. Their results are compatible with numerical Lattice calculations for the G 2 gauge group [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 72%